Bio larvicidal Activity of Noni Leaf and Ylang Flower Infusion on the Death of Aedes aegypti Larvae - Refa Rahmaddiansyah; Salsabila Syafna Aulia; Sukarsi Rusti (Lembaga Pengembangan Kinerja Dosen, 2023)
Dengue Hemorrhagic fever (DHF) is caused by a dengue virus that spreads through the bite of the Aedes aegypti mosquito, which breeds a lot in densely populated areas with humid and warm climates. Anti-mosquito drugs in the form of burns, sprays, lotions, or other types are already widely used, but these anti-mosquito drugs are not entirely beneficial. This research is purely experimental research with Post-test Only Control Group Design by making air spray solution products from noni leaf infusion and cananga flower, which are analyzed descriptively and analytically. Experiments carried out with Randomized Complete Design 1 time repetition to analyze effectiveness. The study used two factors: treatment (P) using infusion products while the control (K) using distilled water. From the results of mixing, it was obtained as much as 400 ml of infusion solution. Obtained in each measurement, there was a reduction in live larvae until the last measurement. Noni leaf contains five flavonol glycosides (flavonoid compounds) as respiratory poisons and a combination of saponins and tannins as stomach poisons that have the killing power against the death of Aedes aegypti larvae. Cananga flower extract itself can resist mosquitoes because of the content of linalool, geraniol and eugenol. This makes a change in the larvae's behavior, where the previously active movement will be slow and eventually will die.